Análise eletromiográfica de músculos do tronco nos exercícios de estabilização de prancha com e sem diferentes superfícies instáveis - Silva, Fabrício Henrqiue de Oliveira (2022)
Different devices are developed with the aim of providing greater EMG activation of the trunk stabilizer muscles, however the inclusion of unstable equipment in trunk stabilization exercise programs should not be based on anecdotal evidence without an understanding of neuromuscular mechanisms. The aim of this study was to analyze and compare the electromyographic activity of the Rectus Abdomen (RA), External Oblique Abdomen (OE) and Eretor Spine (EE) muscles in the ventral plank and lateral plank stabilization exercises, with and without the use of different unstable surfaces (balance board, twist and surf). The sample consisted of 15 male volunteers, physically active, with a mean age of 28±2.28 years, body mass 77.13±4.45 kg, height 178.56±3.77 cm, fat percentage 13. 6±3.84%. As criteria for inclusion, all participants should be considered physically active, or very active. The collection was performed using simple differential surface electrodes, with a gain of 20 times, and recorded using a computerized electromyograph (EMG System do Brasil 830C). The electromyographic signal was analyzed in the temporal domain (Root Mean Square – RMS). To calculate the RMS peak in the CIVM, for further normalization, a moving window of one second was used across the entire signal. Using the computer program GraphPad Prism (version 8.4 – Graphpad Software, Inc) and the data are presented as mean and standard error. In the present study, it was demonstrated that the EMG activity of the abdominal muscles (RA and LE) in the ventral and lateral board stabilization exercises with unstable balance board and twist equipment was significantly higher compared to the same exercises on the floor, while for the EE muscle it was not there were differences. It is concluded that the use of unstable balance and twist surfaces in trunk stabilization exercises (ventral and lateral plank) produced greater EMG activity of the abdominal muscles (RA and LE), while the EMG activity of the EE muscle was not influenced by the use of different unstable surfaces.